The Bidirectional Relationship Between Geopolitical Risks and Volatility Spillovers in Global Energy Markets: An Econometric Study Using DCC-MGARCH Models - Shatha Salem Dily (Research Parks Publishers, 2026)
The research aims to analysis relationship reciprocity between Risks Geopolitics and transfer fluctuations in markets Energy Global, with the focus on group from countries Producer oil gas The Properties Geopolitics volatile, These are : Nigeria, Venezuela, Iraq, Kazakhstan, Azerbaijan, during The period 2011–2024 . Depends Search on index Risks Geopolitical ( GPR Index ) as a variable major To measure level non Stability Political And security, to side returns Prices oil Global As an indicator For markets Energy, That's in framework standard He depends on model decline Self Conditional multi Variables with Link policeman Dynamic ( DCC-MGARCH ) measurement dynamism Contrast Subscriber and connections variable Time between Variables place The study concluded Search to presence relationship correlation dynamism Positive between to rise Risks Geopolitics and increase Fluctuations Prices Energy Global, with contrast in intensity transmission fluctuations between countries place Search Accordingly To the degree Stability Political And the structure yield Oil, as Showed Results that periods crises Global like pandemic COVID -19 and the crisis Russian Ukrainian Enhance from power Interdependence between Risks Geopolitics and markets Energy, In what Reflects sensitive This is amazing markets For shocks Political, And contributes this Search in deepening to understand mechanisms transmission Risks in markets Energy Global Presentation framework standard maybe Accreditation attic in analysis relationship between Stability Geopolitics and fluctuations The markets .